The Effect of Financing and Operational Income on Profit Sharing Return on Mudharabah Deposits for Islamic Commercial Banks - Faulia Anggeraini; Inda Arfa Syera (Publisher Cv. Inara, 2021)
The purpose of this study is to determine the effect of financing and operating income on the return for the results of mudharabah deposits in Islamic commercial banks. The stages of the research method used are the research approach, population and sample, operational definitions, types and sources of data, data collection techniques, data analysis, location and time of research as well as tools and materials. Based on the conclusions found in this study, there is a significant influence of financing variables and operating income variables on the return for the results of Islamic Commercial Bank mudharabah deposits, this is evidenced by the results of research conducted by researchers where the significance value (sig) of 0.001 is smaller than the probability of 0.05 , so it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of financing and operating income on the return on profit sharing from mudharabah deposits of Islamic Commercial Banks.